A Phenomenological Analysis of Marital Satisfaction Dimensions Among SPN Salman ITB Alumni - Nasution, Dia Adlan; Setyowibowo, Hari; Kustimah (IJIP : Indonesian Journal of Islamic Psychology, 2026)
Marriage satisfaction is subjective feelings, attitudes, and behaviors that are judged by couples who surround feelings of happiness, comfort, peace, and harmony in married life. Marriage satisfaction can be achieved by attending a premarital school in order to gain marriage knowledge. SPN Salman ITB is an educational institution that focuses on discussing the science of marriage. The purpose of this research is to see the satisfaction of marriage felt by the premarital school alumni of SPN Salman ITB. This research uses qualitative research methods with a phenomenological approach. The subjects of this study are five married SPN Salman ITB alumni with a minimum marriage age of three years. Data analysis using IPA (Interpretative Phenomenological Analysis) techniques. The results of the study were that the five subjects reported satisfaction with marriage, which was seen from several supporting aspects such as personality problems, communication, conflict management, financial management, role equality, parenting, family and friends, leisure activities, religious orientation, and sexual orientation.